Pengaruh Metode Pembelajaran Whole Language Terhadap Keterampilan Menulis Dalam Mata Pelajaran Bahasa Indonesia Di Kelas IV SDN 52 Pangkalpinang - Rizki Ramadan; M Iqbal Arrosyad; Hevitria (JBES (Journal Basic Education Skills), 2024)
The poor writing abilities of students are what inspired this research. This is due to several factors, including students still being classified as confused or unable to express their thoughts, as well as the lack of initiative of educators to use varied or collaborative methods. This study aims to determine whether the whole language learning method has an effect on writing skills in Indonesian language subjects in class IV SD Negeri 52 Pangkalpinang. The approach used in this research is a quantitative approach with the Quasi experiment method (pseudo experiment) and a research design of a nonequivalent control group. The sampling technique used in this study was the saturated sampling technique, meaning that all populations were included as samples. The sample in this study was class IV, consisting of a control class of 20 students and an experimental class of 20 students. The data collection technique given is the assessment of work (product). The data analysis techniques used are the normality test using the Kolmogorov-Smirnov test, the homogeneity test using the Levene test, and the hypothesis test using the Independent-Sample Test. Based on the results of the study, the data from the hypothesis test shows a sig value (2-tailed) of 0.043 ˂ 0.05. This shows that Ha is accepted, which means that the whole language learning method has an effect on writing skills in Indonesian language subjects in Class IV SD Negeri 52 Pangkalpinang.